Effects of remittances on poverty and human development in developing countries - Chong, Siew Huay (2017)
The issues of the increasing trend of worker’s remittances continue to attract the interest of scholars and policymakers because the growing consensus is that remittance inflows result in economic growth, poverty reduction and human development. The purpose of this study is to examine the effect of remittances on poverty and human development. The first objective analyses the role of human capital in remittances and poverty relationship, whereas the second objective examines the impact of remittances on human development. Both objectives are applied the Generalized Method of Moments (GMM) for the estimation. In the first issue, the main contribution of our work comes from the finding that while remittances reduce poverty, the effect is moderated via education. The impact of remittances on poverty reduces as years of education increases, which show that education exerts a stronger impact than remittances on poverty reduction. The findings imply that the role of remittances in reducing poverty should not be overemphasized particularly in the developing countries, and education is vital in these countries. As to reduce poverty in developing countries, the policy should focus on education by facilitating more schooling opportunities. The remaining control variables such as GDP per capita and financial developments have a negative and significant impact on poverty. Inequality has a positive and significant effect on poverty. The second objective is to examine the impact of remittances on human development. Using the panel data of 67 developing countries from 1981 to 2014, this study aims to answer the question, ‘How does remittances affect human development?’ Results reveal remittances exert a significant positive effect on human development, indicating that a 10 percent increase in remittances will lead to 8.51 percent increase in human development. We also find the effect of other variables on human development in the study. GDP per capita, financial development, inflation and government expenditure have a positive and significant effect on human development. Policy makers need to consider the indicators of human development as a catalyst to human development. Specifically, to improve human development, the policy should concentrate on health, and education in developing countries.